2016
DOI: 10.1038/ncomms13365
|View full text |Cite
|
Sign up to set email alerts
|

Several posttranslational modifications act in concert to regulate gephyrin scaffolding and GABAergic transmission

Abstract: GABAA receptors (GABAARs) mediate the majority of fast inhibitory neurotransmission in the brain via synergistic association with the postsynaptic scaffolding protein gephyrin and its interaction partners. However, unlike their counterparts at glutamatergic synapses, gephyrin and its binding partners lack canonical protein interaction motifs; hence, the molecular basis for gephyrin scaffolding has remained unclear. In this study, we identify and characterize two new posttranslational modifications of gephyrin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 41 publications
5
81
0
Order By: Relevance
“…1B-F). Independent studies have demonstrated that alterations in postsynaptic gephyrin scaffolds are reflected by corresponding changes in GABAergic transmission [20][21][22]. Here, we confirmed that eGFP-gephyrin clusters along the proximal-distal axis of dendrites are associated with GABA A Rs by co-labeling for the g2 GABA A R subunit ( Fig.…”
Section: Cb1 and Cb2 Isoforms Exhibit Differential Effects On Gephyrisupporting
confidence: 84%
See 1 more Smart Citation
“…1B-F). Independent studies have demonstrated that alterations in postsynaptic gephyrin scaffolds are reflected by corresponding changes in GABAergic transmission [20][21][22]. Here, we confirmed that eGFP-gephyrin clusters along the proximal-distal axis of dendrites are associated with GABA A Rs by co-labeling for the g2 GABA A R subunit ( Fig.…”
Section: Cb1 and Cb2 Isoforms Exhibit Differential Effects On Gephyrisupporting
confidence: 84%
“…a2 GABA A R can directly interact with CB and facilitate gephyrin scaffold recruitment at GABAergic postsynaptic sites [12,28]. Hence, we examined in Gabra2 KO mice, where we have reported deficit in gephyrin scaffolding both in hippocampal formation and neocortex [20,27], whether CB overexpression can compensate for the absence of the GABA A R in facilitating gephyrin clustering. We quantified gephyrin cluster density in the first 40 µm segment of dendrite from the soma and found a significant reduction in GCS from Gabra2 KO compared to the WT mice.…”
Section: Cb1 Sh3-can Rescue Gephyrin Scaffolding Defect In Adult-bornmentioning
confidence: 99%
“…Indeed, it remains possible that the reduction in SUMO1 conjugation observed in these mice may be compensated for by SUMO2/3 conjugation, as occurs in SUMO1 knockout mice [64] however, this possibility was not examined in the recent study [13]. We also note that the original studies reporting SUMOylation of synapsin1a [20], gephyrin [36], GluK2 [23], syntaxin1a [19], RIM1α [16] and mGluR7 [41] investigated the functional effects of SUMOylation. Thus, in addition to demonstrating SUMOylation biochemically, those studies demonstrated that SUMOylation affects the target functionally, something which was not addressed in the recent study questioning the functional role of SUMOylation at synapses.…”
Section: Sumo Proteasesmentioning
confidence: 94%
“…Gephyrin is part of a scaffolding protein complex that is required for postsynaptic clustering of GABAA receptors. Gephyrin is SUMOylated and it has been reported that its deSUMOylation promotes the formation of postsynaptic clusters via cross-talk between phosphorylation and acetylation of gephyrin [36].…”
Section: Sumoylation Of Receptors and Interacting Proteinsmentioning
confidence: 99%
See 1 more Smart Citation